PROSES PEMISAHAN ION NATRIUM (Na) DAN MAGNESIUM DALAM BITTERN (BUANGAN) INDUSTRI GARAM - Hapsari, Nur (Jurnal Teknik Kimia, 2008)
Electrodyalises membrane could be used as a separation material of minerals from Bittern (lowsalt content). According to the several literatures data’s proved that the electrodialyses membrane could be used as a separation material for low salt content liquid optimally. So that the minerals content on bittern could be separated and worthwhile optimally. According to the research indicate that the best result of sodium ion (Na) obtained 21,425.90 ppm feeder concentration, 2.8 volt current voltage and 30 minutes operational time and 78.43% rejection. Whereas the Magnesium (Mg) obtained 15,795.30 ppm feeder concentration, 2.5 volt current voltage and 150 minutes operational time and 97.02% rejection.Key word : membrane, cation, anion, voltage, electrodyalises